Data-driven design of two degree-of-freedom nonlinear controllers: The D2-IBC approach. (October 2016) - Novara, Carlo; Formentin, Simone; Savaresi, Sergio M.; Milanese, Mario
Abstract: In this paper, we introduce and discuss the Data-Driven Inversion-Based Control ( D 2 -IBC) method for nonlinear control system design. The method relies on a two degree-of-freedom architecture, with a nonlinear controller and a linear controller running in parallel, and does not require any detailed physical knowledge of the plant to control. Specifically, we use input/output data to synthesize the controller by employing convex optimization tools. We show the effectiveness of the proposed approach on a benchmark simulation example, regarding control of the Duffing system.